2005
DOI: 10.1534/genetics.105.041426
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Half of Saccharomyces cerevisiae Mad1p Mediates Spindle Checkpoint Function, Chromosome Transmission Fidelity and CEN Association

Abstract: The evolutionarily conserved spindle checkpoint is a key mechanism ensuring high-fidelity chromosome transmission. The checkpoint monitors attachment between kinetochores and mitotic spindles and the tension between sister kinetochores. In the absence of proper attachment or tension, the spindle checkpoint mediates cell cycle arrest prior to anaphase. Saccharomyces cerevisiae Mad1p is required for the spindle checkpoint and for chromosome transmission fidelity. Moreover, Mad1p associates with the nuclear pore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 37 publications
(18 reference statements)
6
18
0
Order By: Relevance
“…The CF loss phenotype of pat1Δ strains is complemented by a plasmid expressing PAT1 from its native promoter ( Figure 1A). The frequency of CF loss observed in pat1Δ strain is similar to that reported for deletion of kinetochore genes (Kastenmayer et al 2005;Ma et al 2012). The chromosome-loss phenotype observed in pat1D strain ( Figure 1A) prompted us to examine whether Pat1 associates with CEN DNA.…”
Section: Resultssupporting
confidence: 81%
“…The CF loss phenotype of pat1Δ strains is complemented by a plasmid expressing PAT1 from its native promoter ( Figure 1A). The frequency of CF loss observed in pat1Δ strain is similar to that reported for deletion of kinetochore genes (Kastenmayer et al 2005;Ma et al 2012). The chromosome-loss phenotype observed in pat1D strain ( Figure 1A) prompted us to examine whether Pat1 associates with CEN DNA.…”
Section: Resultssupporting
confidence: 81%
“…In yeast, a C-terminal fragment of Mad1 is sufficient for kinetochore localization and checkpoint signaling (18). Binding between yeast Mad1 CTD and Bub1-Bub3 thus makes a more substantial energetic contribution to the Mad1 kinetochore localization and hence might have higher affinity, allowing its detection.…”
Section: Discussionmentioning
confidence: 99%
“…A C-terminal fragment of yeast Mad1 containing the highly conserved C-terminal domain (CTD) is necessary and sufficient for its kinetochore localization and checkpoint function (18). By contrast, an N-terminal fragment of Xenopus Mad1 lacking the CTD has been shown to localize to kinetochores (19).…”
mentioning
confidence: 99%
“…Interestingly, this role for Nup153 in controlling the mitotic checkpoint appears evolutionarily conserved, since its yeast homologue, Nup1p, is also required for the association of Mad1p with the NPC. 27 Moreover, mutations in nup1 result in altered spindle organization with an increase in multinucleate and anucleate daughter cells as well as failure to exit from mitosis. 47,48 Given a role for Nup153 in development and cancer [17][18][19] it will be interesting to determine how this is related to Nup153's novel function in cell division.…”
Section: Discussionmentioning
confidence: 99%
“…22 The function of the SAC proteins at the NPC has remained largely elusive, although it has been suggested that the NPC may play a role in the duration of the SAC. 26,27 Here, we have examined the effect of altering Nup153 expression in HeLa cells and found that Nup153 levels affect spindle checkpoint activity due to binding of Nup153 to the SAC protein Mad1.…”
Section: Introductionmentioning
confidence: 99%